Muhammadiyah And Social Change In Indonesia: A Historio-Futuristic Study Of The Concepts and Movements - Nasution, Suryadi; Elhusen, Sofwan Karim; Lahmi, Ahmad; Asmaret, Desi; Dahlan, Desrizal (Tarbawiyah Jurnal Ilmiah Pendidikan, 2024)
The purpose of this research is to illustrate the genuine progress of the Islamic movement, which has long disappeared from the vocabulary of modern Muslims. This paper employs a historio-futuristic study, initially touching upon the classical Islamic progress of the Abbasid Caliphate as a mirror of Islamic advancement, which is then converted by drawing the same indicators as a form of real development. Muhammadiyah's commitment and efforts to build a higher quality human civilization clearly have a significant impact, especially in shaping the image of Islam. The accumulation of this movement is manifested in various forms, such as the establishment of thousands of educational institutions, hundreds of clinics and hospitals, thousands of places of worship, and involvement in social activities such as disaster relief and zakat distribution. The exploration of Muhammadiyah's charitable endeavors is demonstrated in a highly universal manner, making it accessible to all people.